Islamic Political Thought in Tafsir Al-Ibriz (Analysis of Leadership Verses) - Al Khanafi, Muh. Imam Sanusi; Tasriyah, Febi; Nurkholifah, Ilma (Rausyan Fikri Journal of Islamic Studies, 2024)
This research aims to analyze Islamic political thought in Tafsir Al-Ibriz, particularly regarding the verses that discuss leadership. Tafsir Al-Ibriz is an important exegetical work in the Islamic tradition and offers unique insights into political and leadership concepts. This research uses a qualitative approach with content analysis methods to examine the interpretation of Qur'anic verses related to leadership, such as Surah An-Nisa' (4:59), Surah Al-Ma'idah (5:55), Surah Al-Baqarah (2:30). The results of the study indicate that Tafsir Al-Ibriz emphasizes the importance of obedience to Allah, the Prophet, and those in authority (ulil amri) as the foundation for just and responsible leadership. The interpretation of the concept of khalifah (caliph) on earth highlights the moral and spiritual responsibilities of leaders in maintaining social balance and justice. Leadership qualities such as gentleness, forgiveness, and consultation are also identified as essential elements in conducting effective and harmonious leadership.This study finds that the political thought in Tafsir Al-Ibriz is not only relevant to its historical context but also provides useful guidance for addressing modern political challenges. This contextual and comprehensive interpretation can serve as a reference in formulating an Islamic leadership concept that is responsive to contemporary social and political dynamics.Keywords: Islamic Political Thought, Tafsir Al-Ibriz, Leadership Verses, Islamic Leadership